2012
DOI: 10.1007/s00572-012-0436-0
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungal communities associated with Masson pine (Pinus massoniana Lamb.) in Pb–Zn mine sites of central south China

Abstract: To advance our understanding of ectomycorrhizal fungal communities in mining areas, the diversity and composition of ectomycorrhizal fungi associated with Masson pine (Pinus massoniana Lamb.) and soil chemistry were investigated in Taolin lead-zinc (Pb-Zn) mine tailings (TLT), two fragmented forest patches in a Huayuan Pb-Zn mineland (HY1 and HY2), and a non-polluted forest in Taolin in central south China. Ectomycorrhizal fungal species were identified by morphotyping and sequence analyses of the internally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…This OTU corresponds to the ectomycorrhizal basidiomycete I. lacera , a typical basidiomycete of primary successions (Jumpponen et al ., ). Even though some reports indicated the presence of Inocybe species on metal‐polluted mine spoils (Huang et al ., ), OTUs corresponding to I. lacera in our study were more abundant in samples with lower Zn, Cd and OM concentrations. Overall, it is noteworthy that the fungal communities in the studied site were dominated by biotrophic species and in particular by ectomycorrhizal fungi, testifying to the importance of these fungal symbionts in disturbed pioneer pine forests.…”
Section: Discussionsupporting
confidence: 54%
“…This OTU corresponds to the ectomycorrhizal basidiomycete I. lacera , a typical basidiomycete of primary successions (Jumpponen et al ., ). Even though some reports indicated the presence of Inocybe species on metal‐polluted mine spoils (Huang et al ., ), OTUs corresponding to I. lacera in our study were more abundant in samples with lower Zn, Cd and OM concentrations. Overall, it is noteworthy that the fungal communities in the studied site were dominated by biotrophic species and in particular by ectomycorrhizal fungi, testifying to the importance of these fungal symbionts in disturbed pioneer pine forests.…”
Section: Discussionsupporting
confidence: 54%
“…In EMs, the fungi provide water and mineral nutrients to the plants and are rewarded with photosynthates by their hosts (Martin & Nehls 2009). Accumulating evidence suggests that EMs can modify physiological and molecular responses of hosts to abiotic and biotic stresses including Cd stress Bellion et al 2006;Krznaric et al 2009;Luo et al 2009aLuo et al ,b, 2011Huang et al 2012;Mrnka et al 2012;Sousa et al 2012). EMs can result in elevated, decreased or unchanged Cd concentrations of host plants depending on host species and fungal isolates (Sell et al 2005;Baum et al 2006;Krpata et al 2009;Mrnka et al 2012;Sousa et al 2012).Therefore, choosing appropriate hosts and fungal partners is essential for remediation of Cd polluted soils.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these fungal genera are the important mycobiont with plants and enforce adaptability of plant for grow in stress conditions, such as metal-contaminated soils. Previous studies showed that Pinus massoniana seedlings were signi cantly resistant to heavy metals than non-mycorrhizal plants when inoculated with S. luteus [15]. Besides Suillus luteus, some mycorrhizal fungi (Suillus bovinus) inoculated plants (e.g.…”
Section: Indicators Of the Representative Fungal Genusmentioning
confidence: 99%
“…Shi et al [10] showed that Pinus thunbergii inoculated with Pisolithus sp1 combined remediation system had higher tolerance index, and the total accumulated chromium (Cr) were 2.83-27.75 fold higher than nonectomycorrhizal (NM) seedlings in pot experiments. As one of 'early stage' ECM fungi that commonly coexist in pioneer coniferous species [11], Suillus species have also proved to be independently evolving in resistance to excessive concentrations of heavy metals, such as zinc (Zn) and cadmium (Cd) [12,13,14,15]. However, how those 'early-stage' ECM fungal species help the hosts to adapt to heavy metal polluted areas and shape the rhizospheric environment remains unclear.…”
Section: Introductionmentioning
confidence: 99%